2019
DOI: 10.18553/jmcp.2019.25.7.765
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Financial Toxicity in Oncology Specialty Pharmacy at a Large Tertiary Academic Medical Center

Abstract: BACKGROUND: Patients with cancer often face financial toxicity. They may face financial distress because of high out-of-pocket costs that in turn can result in delays in treatment, treatment abandonment, and higher overall costs of care, all of which can have have a negative effect on patient care. A specialty pharmacy practice model can play a role in decreasing financial toxicity.OBJECTIVE: To evaluate the patient out-of-pocket costs after enrollment in manufacturer patient assistance programs, copay cards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…Farano et al examined prescription claims for patients who filled oncology specialty prescriptions over the course of six months at the University of Chicago Medicine (UCM) and found that financial assistance was most often applied to TKIs and hematopoietic agents. 11 The study described similar services to the support provided by the embedded MAP specialists in our study and found the average time for insurance and grant approval for patients at the UCM oncology specialty pharmacy was 1.2 days. Our study found a similar median turnaround time for insurance approval of 24 hours and copay assistance approval time of 18 hours.…”
Section: Discussionsupporting
confidence: 56%
“…Farano et al examined prescription claims for patients who filled oncology specialty prescriptions over the course of six months at the University of Chicago Medicine (UCM) and found that financial assistance was most often applied to TKIs and hematopoietic agents. 11 The study described similar services to the support provided by the embedded MAP specialists in our study and found the average time for insurance and grant approval for patients at the UCM oncology specialty pharmacy was 1.2 days. Our study found a similar median turnaround time for insurance approval of 24 hours and copay assistance approval time of 18 hours.…”
Section: Discussionsupporting
confidence: 56%
“…32 , 33 These programs are prevalent in oncology and estimated to cover 87% of all FDA-approved oncology drugs in the US, 33 but broad patient usage statistics for these programs are not known, nor are usage statistics specific to MBC. In retrospective studies in single cancer care institutions, usage estimates range from 12% of all oral oncolytic prescriptions 34 to 32% 35 and 36% 36 of oncology patients filling prescriptions for oral oncolytics at the specialty pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…10 Farano et al demonstrated the effectiveness of an oncology specialty pharmacy practice in an internal HSSP, reporting cost savings of over $300,000 to patients and an average time to insurance approval of 1.2 days for a cohort of 75 patients. 11 In a study by McCabe et al, patients who filled their oral oncolytic prescriptions at an internal HSSP had higher adherence as measured by MPR and PDC, compared with external specialty pharmacies (1.00 vs 0.75; P < 0.001 and 0.95 vs 0.70; P < 0.001, respectively). 9 Shorter TTT was also seen with internal HSSP services (6.85 vs 10.91 days; P = 0.102).…”
Section: What This Study Addsmentioning
confidence: 96%